Variability of Marine Methane Bubble Emissions on the Clayoquot Slope, Offshore Vancouver Island, Between 2017 and 2021 - Marcon, Yann; Römer, Miriam; Scherwath, Martin; Riedel, Michael; Dølven, Knut Ola; Heesemann, Martin (Frontiers in Earth Science, 2022)
Seabed methane gas emissions occur worldwide at cold seeps located along most continental margins. Fluxes of methane gas released from the seabed in the form of bubbles can be extremely variable even over short time intervals. Some factors controlling the variability are still poorly understood. Here, we report on the results of continuous long-term sonar monitoring of bubble emissions at a depth of 1260 m on the Clayoquot Slope, northern Cascadia margin. With a total monitoring duration of four years and a sampling period of 1h, this is by far the longest high temporal resolution monitoring of seabed methane gas release ever conducted. Our results provide evidence that the diurnal and semi-diurnal tides influence the timing of the onset and cessation of bubble emissions. However, gas emissions within the monitoring area are active more than 84% of the time, indicating that tides alone are not sufficient to make venting pause. We hypothesize that the gas fluxes are transient but generally sufficiently high to maintain ebullition independently of the tidally-induced bottom pressure variations. Results also show that the tides do not seem to modulate the vigor of active gas emissions.